PERENCANAAN DAN PERANCANGAN POP CULTURE CREATIVE HUB DI KOTA DENPASAR BALI: Bahasa Indonesia - I Ketut Putra Kurniadi; Made Mas Surya Wiguna; I Kadek Merta Wijaya; I Wayan Wirya Sastrawan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2026)
The development of popular culture in Denpasar City has grown significantly, especially among young communities such as cosplay, gaming, collectors, and digital creators. However, these activities are still temporary and not supported by integrated facilities, resulting in fragmented creative processes and limited sustainability. This study aims to design a Pop Culture Creative Hub in Denpasar as an integrated creative space that accommodates production, collaboration, and commercialization activities. The method used includes literature study, observation, interviews, and precedent study, analyzed through comparative, analytical, and synthesis methods. The design applies a cross-programming approach by integrating creative, commercial, educational, and recreational functions into a flexible and adaptive spatial system. The result is a creative hub that remains active daily and supports the development of a sustainable creative ecosystem in Denpasar.